Studi Mutu Air Sungai Cibaligo Kota Cimahi Provinsi Jawa Barat dengan Metode Indeks Pencemar - Yulia Anggraini; Eka Wardhani (Fakultas Teknik, 2021)
Cibaligo River is the polluted rivers in Cimahi City. The river that flows through three districts and 6 sub-districts in Cimahi City catchment area of 666.19 hectares of watershed with a total length of 7 km. The land use of the district through which this river passes is domestic, trade, agriculture, livestock and industry whose waste will end into the Cibaligo River. The impact of these activities causes the river to be polluted and a decrease in water quality. The purpose of this study was to determine the status of water quality from upstream to downstream which represents the transition, dry, and rainy seasons. Knowledge of water quality status can be used as basic data for controlling water pollution in rivers. The pollutant index (IP) method used in this study is in accordance with the Decree of the State Minister for the Environment Number 115 of 2003 concerning guidelines for determining water quality status. The results showed that the water quality status of the Cibaligo River from upstream to downstream represented that each season was categorized as heavily polluted with the highest index value being in the rainy season at the downstream point. The main contributor that causes river water to be heavily polluted is domestic wastewater, especially the presence of total coliform and fecal coliform that exceed the established quality standards. Based on the results of the research, efforts to tackle domestic waste are needed to improve the quality of this river water.